Hallyu Effect: Korean Lovers Perception Towards Korean Culture - Queen Salsabila; Nadia Rahmadhani (ELITE Association Indonesia, 2023)
This study aims to know: 1) different perceptions of UIN Malang Korean lovers' students about Korean Culture after being affected by Hallyu; 2) is there any interest in learning Korean Culture after being affected by Hallyu on UIN Malang students; 3) UIN Malang Korean lovers’ students' perception toward Indonesian culture after the impact of Hallyu in Indonesia. This study uses the qualitative method. Documentation, observation, and the interview became the techniques used for this research. The result of this study shows that there is a different perception of Korean culture because of the effect of Hallyu. The Korean language and Korean manners are becoming some of the cultures that are interesting to learn. Furthermore, through the effect of Hallyu, there is decreasing in Indonesian culture. Keywords: Hallyu effect; Korean lovers; Korean culture.